2018
DOI: 10.3171/2017.10.spine17947
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of a recurrent juvenile ossifying fibroma of the lumbosacral spine

Abstract: Juvenile ossifying fibroma (JOF) is a rare benign bone tumor that occurs most frequently in the craniofacial bones of children and young adults. There are few case reports that describe its involvement outside the craniofacial skeleton, especially within the spinal column. While JOF is classified as a benign lesion, it may be locally aggressive and demonstrate a high propensity for recurrence, even after resection. Definitive surgical management may be challenging in naive cases, but it is particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…OF has complicated pathological types 19 (Fig. 5), and studies have reported that juvenile ossifying fibroma (JOF) is invasive with a high recurrence rate 20 . There were 18 patients younger than 18 years old with three recurrent cases after surgery in our study.…”
Section: Discussionmentioning
confidence: 67%
“…OF has complicated pathological types 19 (Fig. 5), and studies have reported that juvenile ossifying fibroma (JOF) is invasive with a high recurrence rate 20 . There were 18 patients younger than 18 years old with three recurrent cases after surgery in our study.…”
Section: Discussionmentioning
confidence: 67%
“…While classified as a benign lesion, JOF can be locally aggressive and invade surrounding tissues; it also has a high rate of local recurrence (30%–50%) after resection 4. The mean age at diagnosis of JOF reported in literature is 11 years—with 79% of cases occurring before the age of 15 years 4 5. Two distinct clinicopathologic variants of JOF have been described which show similar biological behaviour.…”
Section: Discussionmentioning
confidence: 99%